Factors associated with the use of health services by elderly men in Brazil: a cross-sectional study - Alana Maiara Brito Bibiano; Vanessa de Lima Silva; Rafael da Silveira Moreira (BMC, 2019)
Abstract Background Studies have shown that older men use health services less frequently than women do. However, there has been little scientific research on this subject, making it necessary to investigate the influence of various factors on the profile of health service use by this population. This study aims to analyze both the profile of health service utilization by elderly Brazilian men and associated factors. Method A population-based cross-sectional study with a secondary database from the National Health Survey (2013) were used. A total of 10,536 male individuals aged 60 years or over were included. The dependent variable was composed of the research questions related to the Use of Health Services, grouped and categorized through the Latent Class Analysis. The independent variables were the factors of predisposition, capacity and health need, organized according to a theoretical model. The association measures were performed by the Rao-Scott test and those of effect by simple and multiple models of multinomial logistic regression. The level of significance was 5%. Results The use of health services was marked by the predominance of sporadic medical appointments in the year previous to the study. It was observed that elderly men from the North, Northeast and Midwest regions, those who were illiterate, those without private health insurance, those who had been diagnosed as having a disease, those with functional difficulties and those with a perception of their health status as very poor had been reluctant to use health services of medium and high complexity in the previous 2 weeks, or accept hospitalization. In the previous year, they had consulted their doctor only sporadically. Conclusion It was noted that unfavorable social issues affected the profile of health service utilization and that the health care of the elderly Brazilian man is centered on the disease and on curative and rehabilitative attention. In this context, intra- and inter-sectorial policies and actions should encourage early contact of the elderly male population with the health services, especially Primary Care services.